An Examination of Washington State Workers' Compensation Claims for Home-Based Health Care Workers, 2006 to 2016: Part 1. Description of Claims and Claimants. Issue 3 (August 2022) - Howard, Ninica L.; Adams, Darrin; Cole, Jena
Home-based health care can be physically and emotionally demanding, resulting in injury or illness. Washington State's workers' compensation compensable claims between 2006 and 2016 were analyzed to describe the characteristics of injured home-based health care (HBHC) providers and the burden created by these injuries. Comparisons were made with clinical health care (CHC) providers, as well as between all compensable claims and work-related musculoskeletal disorder (WMSD) claims. Over 90% of claimants for both HBHC and CHC were female. The mean age of all compensable HBHC claimants (45.7 years) was significantly older than for CHC, with the majority (54.5%) between the ages of 40 and 59. However, HBHC claimants with WMSDs were younger, overall. Across health care type and claim type, the majority of injured care providers were overweight or obese (BMI ≥ 25). The highest mean age occurred among claimants injured from falls, either on the same level or to a lower level (HBHC: 48.3-48.6 years, CHC: 46.1-48.1 years). This same group also had the highest BMIs. WMSDs accounted for 47.3% of HBHC compensable claims and 50.3% for CHC. Falls on the same level were the second most common injury event among HBHC claims. For both HBHC and CHC, back injuries were the most common body part for both claim types (all compensable claims: 28.8% HBHC and 23.9% CHC, WMSD claims: 60.8% HBHC and 47.5% CHC). Overexertion was the injury event most attributed to WMSDs (HBHC: 82.6%, CHC: 71.6), overexertion during lifting being the most prevalent overexertion type (HBHC: 27.8%, CHC: 19.6%).